FACTORS RELATED TO CHOICE OF MOW CONTRACEPTION IN DECISION MAKING IN SETIAJAYA TASIKMALAYA MONTH JANUARY - DECEMBER 2013 - Syafariah, Yayah (Jurnal Kesehatan Bakti Tunas Husada: Jurnal Ilmu-ilmu Keperawatan, Analis Kesehatan dan Farmasi, 2014)
Based on Demography and Population Survey of Indonesia (IDHS) in 2007 amounted to 4.8 percent and the Year 2013 achievement of MOW 7541 people in Indonesia as much as 1.4 percent.Â MOW method (Method Operative Women's) tended to increase although the percentage is still very low compared with other contraceptive methodsThe purpose of this study is to determine what factors associated with contraceptive selection MOW in County Setiajaya Village.The method used in this study is to research methods of correlation and cross sectional approach. The populations in this research are as many as 625 female family planning acceptors of people, while the sample with a random sampling technique 86. Based on the results of this study show that in choosing contraception MOW TalbotVillage Setiajaya Tasikmalaya regency period January to December 2013 have mostly aged between 20-35 years as many as 51 people (59.30%), whereas most 63 knowledgeable enough people (73.26%), and most of the low economic status as much as 57 people (66.26%).Conclusion this study proved that there is parity with the election relations MOW contraception in County village of Tasikmalaya Setiajaya period January to December 2013.